DRAINMOD simulation of paddy field drainage strategies and adaptation to future climate change in lower reaches of the Yangtze river basin. (12th January 2021) - Awad, Ahmed; Luo, Wan; Zou, Jiarong
Abstract: The DRAINMOD model was used to simulate the current and future water balance in the Yanyun Irrigation District, China. Projections of future climate in the district (2021:2050) show that annual maximum and minimum temperatures will increase by [1.09 and 1.15 °C] under the representative concentration pathway RCP4.5 and [1.34 and 1.39 °C] under RCP8.5, besides more frequency of one‐day peak precipitation events. DRAINMOD simulations revealed that future annual runoff will increase by 33.3% (RCP4.5) and 36.9% (RCP8.5), while groundwater tables will drop by 6% (RCP4.5) and 14.5% (RCP8.5). Future hydrology has been resimulated, but with increasing the capacity of surface depressions in an attempt to minimize adverse impacts of climate change, and results have been checked twice: under proper and improper subsurface drainage practices. Under proper subsurface drainage practices, it was revealed that future runoff will decrease by 25.3% (RCP4.5) and 23.6% (RCP8.5), which will cause a rise in groundwater tables to desired levels, while in contrast, improper subsurface drainage practices will increase future runoff by 13.7% (RCP4.5) and 2.8% (RCP8.5), all compared to future values before adaptation. Therefore, proper drainage strategies are a vital tool that helps to cope with climate change in agricultural lands and mitigate future runoff rates. Abstract : Résumé: Le modèle DRAINMOD a été utilisé pour simuler le bilan hydrique actuel et futur dans le district d'irrigation de Yanyun, en Chine. Les projections du climat futur dans le district (2021: 2050) montrent que les températures annuelles maximales et minimales augmenteront de [1.09 et 1.15 °C] sous la voie de concentration représentative RCP4.5 et [1.34 et 1.39 °C] sous RCP8.5, en plus d'une fréquence accrue dans les événements de précipitations de pointe d'une journée. Les simulations DRAINMOD ont révélé que le ruissellement annuel futur augmentera de 33.3% (RCP4.5) et 36.9% (RCP8.5), tandis que les nappes phréatiques chuteront de 6% (RCP4.5) et de 14.5% (RCP8.5). L'hydrologie future a été reconstituée, mais avec l'augmentation de la capacité de dépression de surface dans une tentative de minimiser les effets néfastes du changement climatique, et les résultats ont été vérifiés à deux reprises: dans le cadre de pratiques de drainage souterraines appropriées et inappropriées. Dans le cadre de pratiques de drainage souterraines appropriées, il a été révélé que le ruissellement futur diminuera de 25.3% (RCP4.5) et de 23.6% (RCP8.5), ce qui entraînera une élévation des nappes souterraines aux niveaux souhaités, tandis qu'en revanche, des pratiques de drainage souterraines inadéquates augmenteront le ruissellement futur de 13.7% (RCP4.5) et de 2.8% (RCP8.5), le tout par rapport aux valeurs futures avant adaptation. Par conséquent, des stratégies de drainage appropriées sont un outil essentiel qui aide à faire face au changement climatique dans les terres agricoles et à atténuer les taux de ruissellement futurs.